Clinical characteristics of Chlamydia psittaci pneumonia and predictors analysis of severe patients: a retrospective observational study - Wu, Ling; Chen, Liang; Peng, Liping; Liu, Chun; He, Shengyang; Xie, Lihua (Frontiers in Medicine, 2025)
BackgroundWith this study, we aimed to explore the clinical features, laboratory examinations, imaging features, and severe predictors of Chlamydia psittaci pneumonia to identify the disease early, shorten the course of illness, and improve prognosis.MethodsWe retrospectively reviewed the clinical data of 39 patients diagnosed with Chlamydia psittaci pneumonia and 39 patients with non-psittacosis community-acquired pneumonia at the Third Xiangya Hospital of Central South University from December 2018 to April 2021. We collected the remaining medical serum to analyze cytokines that are associated with disease-related inflammation. We used the R software to perform statistical analysis.ResultsCompared to the non-psittacosis community-acquired pneumonia group, the common Chlamydia psittaci pneumonia group exhibited more severe symptoms, including a longer duration of hyperthermia. Most patients experienced dyspnea, as well as extrapulmonary symptoms such as fatigue, muscle soreness, and diarrhea. There were also significant increases in levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), lactate dehydrogenase (LDH), C-reactive protein, and procalcitonin, while hemoglobin (Hb) and albumin (ALB) levels decreased significantly. Primary lung imaging features included consolidation and exudation, with nodules and cavities being rare. These changes were even more severe in the severe Chlamydia psittaci pneumonia group, with further increased levels of myoglobin and a larger spread of lesions in the lungs. Additionally, the Th1 inflammatory factor INF-γ was elevated in the Chlamydia psittaci pneumonia group.ConclusionFatigue, myalgia, low Hb, low ALB, high ALT, and high AST are predictors of Chlamydia psittaci pneumonia. Fast respiratory rates, low Hb, high LDH, significant involvement of multiple lobes, high Sequential Organ Failure scores, and high Acute Physiological and Chronic Health scores are predictors of severe Chlamydia psittaci pneumonia. The increase of INF-γ may be related to the condition.